Unilateral Vocal Cord Paresis During Sleep Endoscopy - Viola, Francesca C (Cureus, 2021)
Abnormalities of vocal cord motion in children with obstructive sleep apnea (OSA) who undergo drug-induced sleep endoscopy (DISE) are not frequently described. A 17-year-old female with a history of asthma, reflux, and bipolar disorder had a history of poor sleep. Polysomnography (PSG) showed apnea-hypopnea index (AHI) of 13.9/hr, obstructive AHI 10.3/hr, and oxygen saturation nadir 87%. Physical exam showed BMI 34 and 3+ tonsils. She underwent DISE with propofol infusion, which showed partial obstruction at the palatine and lingual tonsil levels, a posteriorly displaced epiglottis along with immobility of the left vocal cord. Tonsillectomy was performed as planned. At her post-op visit, laryngoscopy showed normal vocal cord motion bilaterally. Post-operative PSG was improved.